A Two-Step Continuous-Control-Set Mpc for Modular Multilevel Converters Operating with Variable Output Voltage and Frequency - Diaz-Diaz, M (Institute of Electrical and Electronics Engineers Inc., 2023)
This article presents a new enhanced single-stage two-step continuous control set model predictive control (CCS-MPC) algorithm, for modular multilevel converters (MMCs) operating with variable output frequency at the ac port. The proposed two-step CCS-MPC allows the implementation of feed-forward compensation of the one-step ahead perturbations at the ac side, using an algorithm based on the Moore-Penrose pseudoinverse matrix. Limitations of the current and voltages in the MMC clusters are implemented to avoid overmodulation and overcurrents, being the solution of the constrained CCS-MPC online solved using the active-set method. Without losing generality, the experimental validation of the single-stage CCS-MPC is performed using an 18-cell MMC prototype, driving a 7.5-kW cage induction machine operating in a wide speed range. A dSPACE MicroLabBox platform is used to control the MMC-based drive by implementing the CCS-MPC algorithm, the modulation stage and the active-set method. It is experimentally demonstrated that the compensation of the low-frequency perturbations allows a considerable reduction in the required circulating currents at the low-frequency operation of the drive. Reduction in the capacitor voltage ripple, improved efficiency, and a smaller total harmonic distortion in the output currents are also achieved with the proposed single-stage two-step CCS-MPC. © 1986-2012 IEEE.